СТРУКТУРА ТА ФУНКЦІЇ СИСТЕМ ЕНЕРГОМЕНЕДЖМЕНТУ МІКРОМЕРЕЖІ В УМОВАХ ПІДКЛЮЧЕННЯ ДО СИСТЕМИ РОЗПОДІЛУ ЗГІДНО ДО ВИМОГ МІЖНАРОДНИХ СТАНДАРТІВ - Блінов, І.В.; Палачов, С.О.; Парус, Є.В.; Клименко, О.Г. (Інститут електродинаміки Національної академії наук України, 2025)
This publication is devoted to the study of the structure and functions of microgrid energy management systems in accordance with current international standards, particularly in the context of reducing electricity costs for microgrid users. A review of terminology related to microgrid operation control systems is provided. The hierarchical structuring of goals and control tasks for microgrid operation is analyzed under varying degrees of constraints on electricity supply from the distribution grid. The paper investigates approaches to microgrid operation planning based on different optimization criteria and identifies the key components of optimization procedures. The structure of energy management system functions for controlling the energy equipment of a microgrid connected to the distribution system is defined.